2009
DOI: 10.1029/2009gc002411
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and compositional changes in the skeletons of new coral recruits reared in acidified seawater: Insights into the biomineralization response to ocean acidification

Abstract: [1] We reared primary polyps (new recruits) of the common Atlantic golf ball coral Favia fragum for 8 days at 25°C in seawater with aragonite saturation states ranging from ambient (W = 3.71) to strongly undersaturated (W = 0.22). Aragonite was accreted by all corals, even those reared in strongly undersaturated seawater. However, significant delays, in both the initiation of calcification and subsequent growth of the primary corallite, occurred in corals reared in treatment tanks relative to those grown at am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
164
4
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 205 publications
(179 citation statements)
references
References 47 publications
(59 reference statements)
10
164
4
1
Order By: Relevance
“…This suggests that the planulae may be highly susceptible to the effects of seawater acidification during the period of early calcification in metamorphosis. We suggest that the decline in calcification rates found by Cohen et al 2009 andAlbright et al 2008 were greater compared to our experiment because our treatment exposures did not cover the initial calcification period.…”
Section: Calcification In Primary Polypscontrasting
confidence: 40%
See 2 more Smart Citations
“…This suggests that the planulae may be highly susceptible to the effects of seawater acidification during the period of early calcification in metamorphosis. We suggest that the decline in calcification rates found by Cohen et al 2009 andAlbright et al 2008 were greater compared to our experiment because our treatment exposures did not cover the initial calcification period.…”
Section: Calcification In Primary Polypscontrasting
confidence: 40%
“…However, net productivity was observed to decrease in adult corals under higher temperatures and elevated pCO 2 by both Crawley et al (2010) and Anthony et al (2008). The cumulative increase in metabolism of primary polyps in the high temperature and low pH could be associated with the additional energy required to drive proton pumps to maintain sufficient pH-levels in the calcifying space (Cohen et al, 2009) or alternatively, an inefficiency of photosynthesis (Buxton et al, 2009) and more severe photorespiration compared to low pH and subsaturated light conditions (Crawley et al, 2010). A speculative conclusion is that combined high temperatures and low pHs reduce biomass because of the reduction of phosphoglycolate phosphatase and resulting increase in the inhibition of carbon fixation via phosphoglycolate in the Calvin cycle (c.f.…”
Section: Development Of Primary Polypsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the saturation state of the surrounding seawater alone does not control coral calcification as corals can continue to calcify in under-saturated conditions (e.g. Marubini and Atkinson, 1999;Cohen et al, 2009) or dissolve in super-saturated conditions (e.g. Herfort et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…During the past two decades, it has been shown that the basic skeletal units, crystal-like fibers, are built by repeated micrometer growth steps that can be visualized by etching polished skeletal surfaces (14)(15)(16). The resulting macroscopic skeletal structures of individual corals are strongly influenced by environmental factors, especially light (17), physical flow (18), and carbonate saturation (19). The aggregate of these individual coral skeletons is the basis for reef formation in tropical and subtropical shallow ocean margins, and is critical for the sustaining the diversity of fauna found in those environments (20).…”
mentioning
confidence: 99%